The physics and psychophysics of music : an introduction. (4th ed.) - Roederer, Juan G. (Springer, 2017)
The Science of Music and the Music ofScience: A Multidisciplinary Overview. Sound Vibrations, Pure Tones,and the Perception of Pitch. Sound Waves, Acoustic Energy, and thePerception of Loudness. Generation of Musical Sounds, ComplexTones, and the Perception of Timbre. Superposition and Successions of ComplexTones and the Integral Perception of Music.